Research Advances and Future Directions of Biotechnology in the Treatment of Myasthenia Gravis - Jiaqi Lin (International Journal of Public Health and Medical Research, 2026)
Myasthenia gravis (MG) is an autoimmune disease with a core pathological mechanism involving specific attacks by the immune system on proteins at the neuromuscular junction. This study reveals that our understanding of its pathogenesis has expanded beyond mere neuromuscular transmission dysfunction to encompass multiple aspects, including the dysregulation of immune regulatory networks, abnormal activation of the complement system, and damage mediated by specific autoantibodies. While conventional pharmacological therapies can alleviate clinical symptoms and control disease progression, they generally suffer from significant long-term side effects, substantial individual variability in patient response, and an inability to achieve a cure in most patients. In contrast, targeted biologics enable precise intervention in key disease pathways, whereas stem cell therapy and gene therapy offer novel strategies for restoring immune tolerance and achieving long-term functional control of the disease, collectively advancing the therapeutic paradigm from broad nonspecific immunosuppression toward precision medicine. This study reviews the pathogenesis of MG, systematically outlines the current applications of conventional drugs, targeted biologics, thymectomy, and gene therapy in its treatment, analyzes existing therapeutic challenges, and explores future directions, such as precision medicine and novel targeted therapies.